A Brief History of Liberty—And Its Lessons*. Issue 1 (2nd January 2016) - Pettit, Philip
Abstract: Classical republicanism and classical liberalism divide on the understanding of freedom, the one taking it as non-domination, the other as non-interference. And essentially the same division survives today, with serious policy implications, between neo-republicanism and neo-liberalism.